Towards an IoT-Based Architecture for Monitoring and Automated Decision-Making in an Aviary Environment - Lopes, Vinícius C.; Oliveira, Roberto Felício de; Graciano Neto, Valdemar Vicente (Anais do Congresso Brasileiro de Agroinformática (SBIAGRO), 2021)
Internet of Things (IoT) is a prominent technology in which everyday objects can be equipped with identifying, sensing, networking, and processing capabilities that allow them to communicate with each another and with other devices and services over the Internet to achieve some goal. In agribusiness, the use of technologies, such as IoT, is called precision livestock farming, which includes the use of different technologies in production and care of livestock animals. Brazil is one of the largest poultry producers in the world, being the first in exportation. Despite that, poultry production faces difficulties due to sensitivity that birds have to numerous environmental factors in aviaries, such as lightning, sounds, harmful gases, air humidity, food quality and clean water. When these variables are not well controlled, problems in meat quality and poultry production are likely to occur. As a result, farmers may face severe financial losses. Thus, providing a healthy environment is essential, and to achieve this, accurate monitoring and fast decision making are required in order to solve the problem as soon as possible. In this paper a detailed process of requirements elicitation and architectural design for IoT-Based aviary monitoring systems is proposed along with an informal literature review from the area. As preliminary results, we delivered a requirements document with functional and nonfunctional requirements closer to the real needs of farmers and an architectural proposal that can be used as a reference for further studies.